The role of the extensive margin in export of Turkey: A comparative analysis - Altan Aldan; Olcay Yucel Culha (Central Bank Review (CBR), 2016)
We examine the role of extensive margin, in other words, new export products and destinations, on Turkish export performance between 1995 and 2013, in comparison with some other countries. We use two complementary methods together with several extensions taking into account critiques in the literature. Our results suggest that, Turkey was quite successful in extending its extensive margin compared to other developing countries. The growth of extensive margin mostly comes from entering into new markets. Nevertheless, the level of the extensive margin is still low as of 2013 compared to the other countries. Turkey still has important opportunities to increase its exports via extensive margin especially in products.
Keywords: F10; F14; O57; 330; Turkey; Exports; Extensive margin